Release of Silver and Copper Nanoparticles from Polyethylene Nanocomposites and Their Penetration into Listeria Monocytogenes - Rabagliati-Canessa, F; Paez-Collio, M; Paez-Collio, M; Gulppi-Cabra, M; Gulppi-Cabra, M; Azocar-Guzman, M; Azocar-Guzman, M; Tamayo-Villarroel, L; Tamayo-Villarroel, L; Zapata-Ramirez, P (Elsevier BV, 2014)
Since infection is a major cause of death in a patient whose immune responses have been compromised (immunocompromised patient), considerable attention has been focused on developing materials for the prevention of infections. This has been directed primarily at suppressing or eliminating the host s endogenous microbial burden and decreasing the acquisition of new organisms. In this study, the antibacterial properties of two nanocomposites, polyethylene modified with silver nanoparticles (PE-AgNps) or copper nanoparticles (PE-CuNps), against Listeria monocytogenes have been investigated. In order to elucidate the antibacterial mechanism, specifically whether this mechanism corresponds to bactericidal or bacteriolytic activities, we have determined the extent of release of metal ions (Ag+ and Cu 2 +) and, also, the morphology of the bacteria. The metal ion release from nanocomposites was followed by inductively coupled plasma spectrometry and the morphology of the bacteria was revealed through examination of ultramicrotomed sections of bacteria in a transmission electron microscope. The study of metal ion release from the nanocomposites shows that for both nanocomposites the amount of ions released varies with time, which initially displays a linear behavior until an asymptotic behavior is reached. Further, TEM images show that silver nanoparticles (AgNps) and copper nanoparticles (CuNps), which are released from the nanocomposites, can penetrate to the cell wall and the plasma membrane of bacteria. Resulting morphological changes involve separation of the cytoplasmic membrane from the cell wall, which is known to be an effect of plasmolysis. It was revealed that the antibacterial abilities of the two nanocomposites against L. monocytogenes are associated with both bactericidal and bacteriolytic effects. © 2014 Published by Elsevier B.V.